Cu-Nanoclusters as Emerging Catalyst in Organic Synthesis - Pal, Amit; Biswas, Sourav; Sahoo, Basudev; Negishi, Yuichi (Synlett, 2025)
In recent decades, nanocluster research has rapidly advanced. Though Cu nanoclusters are relatively new to the field, their use in chemical catalysis has expanded the potential applications of these materials. The reactivity of Cu nanoclusters is primarily determined by their precisely controlled structural architecture and surface-to-volume ratio. However, these factors are prone to change, significantly impacting their catalytic properties. Therefore, a comprehensive understanding of these parameters is crucial to guide future research efforts and develop new Cu nanoclusters with broader applications.1 Introduction2 Click Reaction3 Carbamate Synthesis4 Ullmann (C–N) Coupling5 Indolizine Synthesis6 Hydrogenation Reaction7 Sonogashira Reaction8 Hydroboration Reaction9 Decarboxylative Oxidation of Carboxylic Acids10 Conclusion
Keywords: NCs; copper; atom-precise; metal; structure